EFFECT OF REAL EARNING MANAGEMENT ON COMPANY PERFORMANCE (EMPIRICAL STUDY ON GO PUBLIC COMPANIES INDEXED ON JII) - Ningsih, Suhesti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2017)
The purpose of this study is to determine the effect of real earning management on corporate performance on companies indexed in JII period 2013-2015. The research method used is explanatory which is designed to analyze earnings management practice for 3 years. The populations in this study are companies listed on the BEI in the Jakarta Islamic Index (JII) in 2013-2015. The technique of determining the sample in this study is purposive sampling. The data source used in this study is the annual financial statements published by publicly listed indexed companies in JII and published during the year 2013 to 2015. The results of the research with F test shows that together proxies real earning management that is cash flow operational, production cost and discretionary expense affect the performance of the company proxies with ROA. From the result of t test is known proxy production cost and discretionary expense have an effect on to company performance, while proxy Cash flow operational does not have an effect on to company performance. Keywords: Real Earning Management; CFO; PROD; DISCR; ROA